FEASIBILITY FOR ULTRASOUND‐GUIDED INJECTION OF THE COLLATERAL LIGAMENTS OF THE DISTAL INTERPHALANGEAL JOINT IN HORSES. Issue 3 (13th January 2016) - Lewis, Danyse; Scott, Mike; Fischer, Carrie D.; Bond, Stephanie L.; Léguillette, Renaud
Abstract : Desmitis of the collateral ligament of the distal interphalangeal joint is a cause of lameness in performance horses. The objective of this prospective, experimental, ex vivo feasibility study was to evaluate the success of ultrasound‐guided injection of the collateral ligaments of the distal interphalangeal joint in the equine forelimb. Seventy‐six ultrasound‐guided dye injections of the collateral ligament of the distal interphalangeal joint were performed on horses' cadaver limbs. The hooves were sectioned transversely to verify the location of the dye relative to the collateral ligaments and surrounding structures. Evaluations of transverse sections were performed independently by two experienced observers. A scoring system was used to assess injection of the collateral ligament of the distal interphalangeal joint at the proximal, middle, and distal aspect over the length of the ligament. The collateral ligament was injected at any point in 97.4% of cases. The ligament was injected over the entire scored length in 43.2% of cases (32/74), over two scored length areas in 45.9% of cases (34/74), and in one area in 10.8% of cases (8/74). The distal interphalangeal joint and the common digital extensor tendon were also injected in 81.6% (62/76) and 43.4% (33/76) of the cases, respectively. Use of the ultrasound had a positive and negative predictive value of 98% and 9%, respectively. In this study, ultrasound guidance was useful for confirming injection of the collateral ligament of the distal interphalangeal joint but did not prevent injecting the distal interphalangeal joint and the common digital extensor tendon.